2019
DOI: 10.3390/nano9060832
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Optical Properties of CsPbX3/ZIF-8 Composites for Wide-Color-Gamut Display

Abstract: All-inorganic CsPbX3 (X = Cl, Br, and I) perovskite quantum dots (QDs), an emerging type of luminescent materials, have drawn extensive attention in recent years. However, the amelioration of their stability is becoming a critical issue. Herein, we present a facile and efficient approach to prepare novel perovskite QDs/metal–organic frameworks (CsPbX3/ZIF-8) composites under ambient-atmospheric conditions. The obtained composites exhibit better properties including high photoluminescence (PL) quantum yields (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…It should be noted that the values of t av for CsPbBr 3 and CsPbBr 1.2 I 1.8 NP, embedded in the FAU oxide matrix are significantly higher than that for QD of individual CsPbBr 3 and CsPbBr 1.2 I 1.8 , respectively 5-10 ns [32,41,42] and 27 ns [43]. The t av increase could be associated with the confinement effect on the electronic properties of a semiconductor in the dielectric matrix.…”
Section: Resultsmentioning
confidence: 91%
“…It should be noted that the values of t av for CsPbBr 3 and CsPbBr 1.2 I 1.8 NP, embedded in the FAU oxide matrix are significantly higher than that for QD of individual CsPbBr 3 and CsPbBr 1.2 I 1.8 , respectively 5-10 ns [32,41,42] and 27 ns [43]. The t av increase could be associated with the confinement effect on the electronic properties of a semiconductor in the dielectric matrix.…”
Section: Resultsmentioning
confidence: 91%
“…Guo et al presented the synthesis of CsPbBr 3 /ZIF-8 composites by a facile stirring approach (Figure 9c). [69] The resulted composites showed improved stability by comparison to pure PQDs. Notably, a remote-type WLED was formed by placing the CsPbBr 3 /ZIF-8@PMMA and CsPbBr 1.2 I 1.8 /ZIF-8@PMMA films on a blue InGaN chip (445 nm), with the performance including CCT of 8461 K, LE of 12.85 lm•W −1 and a wide gamut covering 137% of the National Television System Committee (NTSC) standard (Figure 9d), implying the potential for white-light backlit display.…”
Section: Mof⊃pqds Phosphormentioning
confidence: 95%
“…In addition to the in situ growth of PQDs in MOFs, the post-synthetic strategy has also been adopted recently to prepare PQDs@MOF composites. By directly physical mixing and surface absorbance of as-prepared PQDs with MOFs, many researchers claimed the broad prospect of PQDs@MOF hostguest system in the applications of photocatalysis, [68] widecolor-gamut display, [69] and optoelectronic field. [19f ] Recently, Su et al reported a post-synthetic protocol of obtaining core-shell CsPbBr 3 @zeolitic imidazolate framework nanocomposites.…”
Section: Mof⊃pqds Phosphormentioning
confidence: 99%
“…Several properties have been studied for ZIF-8, such as its structural, optical and electronic properties [22][23][24][25][26][27]. However, the thermal stability of ZIF-8 is not enough since, in several industrial operations, harsh conditions-for instance: high pressures, high temperature, and the existence of oxidants-are needed.…”
Section: Introductionmentioning
confidence: 99%